# Uf sentence example

uf

- UF bottle screw CL components BT rigging component RT girder chain River Ant wherry Norfolk wherries sized up to 50ft x 12ft.
- ukx(n-2) ï¿½ Taking the first polar with regard to y (n - k) (a f) xa x -k-l ay+ k (af) k-l ay -k (ab) (n -1) b12by n kn-2k-1 n-1 k(n-2) =k(n- 2)a u x u5+nax ayux and, writing f 2 and -f l for y1 and 3,21 (n-k)(a f) k+ta i k-1 + k (n - 1)(ab)(a f) k-1 (b f)4 1 k by-2 = (uf)u xn-2k-1?
- Moreover the second term on the left contains (a f)' c -2b z 2 = 2 (a f) k-2b x 2 - (b) /0-2a 2 ï¿½ if k be uneven, and (af)?'bx (i f) of) '-la if k be even; in either case the factor (af) bx - (bf) ax = (ab) f, and therefore (n-k),bk+1 +Mï¿½f = k(n-2)f.(uf)uxn-2k-1; and 4 ' +1 is seen to be of the form f .14+1.
- With hydroflouric acid it yields uranous fluoride, UF 4, which forms double salts of the type MF UF 4.
- di g d tan i g dt - v cos i ' and now (53) dx d 2 y dy d2xdx Cif dt 2 dt dt2 _ - _ gdt' and this, in conjunction with (46) dy _ d y tan i = dx dt/dt' (47)di d 2 d d 2 x dx sec 2 idt = (ctt d t - at dt2) I (dt), reduces to (48) Integrating from any initial pseudo-velocity U, (60) du t _ C U uf(u) x= C cos n f u (u) y=C sin n ff (a); and supposing the inclination i to change from 0, to 8 radians over the arc.Advertisement
- uf Ui = (u2 u1), (40) (i.e.
- Thus if the particle start at time t=o from the origin, with the component velocities uf, Vo, we have x=u~t, y_~vct~1/8gt5.
- revived it by the foundation of the university uf Salainanca, which dates from 1245.
- (63) 0-0 =Cg cos n f u Au), 6 (4) tan 4 - tan g =Cg sec ?if u f(u)' But according to the definition of the functions T, S, I and D of the ballistic table, employed for direct fire, with u written for v, (65) ('u du _ du T(U) - T(u), J uf(??) - f g (66) ru du J f(u) (67) g du f uf(u) and therefore (68) t=C [T(U) - T(u)], (69) x = C cos n [S(U) - S(u)1, (70) y =C sin n [S(U) - S(u)], 0-8= C cos n [I (U) - I (u)], (72) tan 0.
- ukx(n-2) Ã¯¿½ Taking the first polar with regard to y (n - k) (a f) xa x -k-l ay+ k (af) k-l ay -k (ab) (n -1) b12by n kn-2k-1 n-1 k(n-2) =k(n- 2)a u x u5+nax ayux and, writing f 2 and -f l for y1 and 3,21 (n-k)(a f) k+ta i k-1 + k (n - 1)(ab)(a f) k-1 (b f)4 1 k by-2 = (uf)u xn-2k-1?Advertisement
- Moreover the second term on the left contains (a f)' c -2b z 2 = 2 (a f) k-2b x 2 - (b) /0-2a 2 Ã¯¿½ if k be uneven, and (af)?'bx (i f) of) '-la if k be even; in either case the factor (af) bx - (bf) ax = (ab) f, and therefore (n-k),bk+1 +MÃ¯¿½f = k(n-2)f.(uf)uxn-2k-1; and 4 ' +1 is seen to be of the form f .14+1.